External Debt Histories of Ten Low-Income Developing Countries : Lessons from Their Experience - Ross, Kevin (IMF Working Papers; Working Paper, 1998)
The external debt burden of many low-income developing countries has increased significantly since the 1970s. Developments in a sample of ten countries show that the main factors behind the buildup of debt were (1) exogenous (adverse terms of trade shocks or weather), (2) a lack of sustained macroeconomic adjustment and structural reforms, (3) nonconcessional lending arid refinancing policies of creditors, (4) inadequate debt management, and (5) political factors (civil war and social strife). Future policies should limit the need for external financing and create an environment conducive to diversifying export growth, managing debt more prudently, and basing economic projections on more cautious assumptions.